Effects of a model for multidisciplinary peer observation of teaching in teacher professional development and in nurturing a reflective school. Issue 1 (2nd January 2023) - Mouraz, Ana; Pinto, Daniela; Cristina Torres, Ana
ABSTRACT: Peer observation of teaching has for long been defended as a valuable device of professional and institutional development in higher education, but is almost unexplored at primary- and secondary-level schools. This paper introduces a model for multidisciplinary peer observation of teaching that has been developed and implemented in a professional development programme in two Portuguese school clusters of basic and secondary education in collaboration with its teachers. After four years of developing the programme in these school clusters, a case study was conducted through a qualitative analysis of observation guides completed throughout the years (N = 563) to identify perceived effects of participating in the programme for both teacher professional development and reflective practices. The programme emerged as a powerful initiative to foster teacher collaboration, innovation, and reflection for improving practices. Implications related to current national curriculum and educational policies are discussed.